FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM MEMBELI SAYURAN ORGANIK - Sovranita Reza Mahesa Devi; Georgius Hartono (Agric, 2015)
This research on factors affecting consumer decision in buying organic vegetables has been completed from December 20, 2013 to February 20, 2014 in the village Kutowinangun, sub district Tingkir, Salatiga. The purpose of this study was to determine the effect of age, the amount of family income (household income) per month, the number of family members, the level of formal education, the intensity associated with the reference group, and motivation (reason) for purchasing organic vegetables. This study used a quantitative approach whith incidental sampling tehnique. Samples divided into two groups, namely: 1) consumers who bought organic vegetables, and 2) consumers who did not buy organic vegetables (bought non-organic vegetables). This study used binary logistic regression. The data collected was primary data obtained from interviews for consumers used questionnaires, while secondary data taken by noting literature and other documents related to the study. The results showed that: the amount of family income per month, the level of formal education, the intensity associated with the reference group, and motivation purchase had significant effect (positive) to the consumer’s decision to buy organic vegetables, and age and number of dependents did not significantly affect to the consumer’s decision to purchase organic vegetables.